COVID-19 and Dengue Co-infection in a Young Girl: A Case Report - Hossain, Homayra Tahseen; Tasnim, Refaya; Khatun, Halima; Noor, Nawsabah; Rishad, Mahbub Mayukh; Islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2021)
During COVID-19 pandemic, the increasing incidence of dengue in Monsoon season has become a further threat especially in the dengue endemic countries of Southeast Asia like Bangladesh. Co-infection of dengue with COVID-19 has created a number of practical challenges to combat the diseases simultaneously, especially at a time when healthcare resources are already exhausted tackling the COVID pandemic. We are presenting the case report of a 14 year old girl who suffered from both RT-PCR positive COVID -19 infection & NS1 positive Dengue. She was managed in a Private Hospital of Dhaka as Dengue fever Group C (due to severe plasma leakage) with severe COVID-19 infection (as required oxygen therapy). She had a critical course of illness, having continued fever, cough, breathlessness, desaturation along with thrombocytopenia & plasma leakage. However, to our great satisfaction, the patient was ultimately improved & could be discharged in a happy face. Bangladesh J Medicine July 2022; 33(1) : 104-108